Evidence that EZH2 Deregulation is an Actionable Therapeutic Target for Prevention of Prostate Cancer - Burkhart, Deborah L. (Cancer Prev Res (Phila), 2020)
Chemoprevention trials for prostate cancer (PCa) by androgen receptor or androgen synthesis inhibition have proven ineffective. Recently, it has been demonstrated that the histone methlytransferase, EZH2 is de-regulated in mouse and human high-grade prostatic intraepithelial neoplasia (HG-PIN). Using pre-clinical mouse and human models of PCa, we demonstrate that genetic and chemical disruption of EZH2 expression and catalytic activity reversed the HG-PIN phenotype. Further, inhibition of EZH2 function was associated with loss of cellular proliferation and induction of Tp53 dependent senescence. Together, these data provide provocative evidence for EZH2 as an actionable therapeutic target towards prevention of prostate cancer.